2020
DOI: 10.1016/j.neuroscience.2020.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Meditation Increases the Entropy of Brain Oscillatory Activity

Abstract: We address the hypothesis that the entropy of neural dynamics indexes the intensity and quality of conscious content. Previous work established that serotonergic psychedelics can have a dysregulating effect on brain activity, leading to subjective effects that present a considerable overlap with the phenomenology of certain meditative states. Here we propose that the prolonged practice of meditation results in endogenous increased entropy of brain oscillatory activity. We estimated the entropy of band-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
5

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 68 publications
(39 reference statements)
4
30
5
Order By: Relevance
“…As predicted, we found a difference in entropy, with lower amounts of entropy during meditation compared with mind wandering. This finding contrasts with that of Vivot et al (2020), who found increased entropy of band-specific oscillations during three styles of meditation-Himalayan Yoga (FA), Vipassana (OM), and Isha Shoonya Yoga (non-dual). One reason for the difference in findings is that Vivot et al (2020) calculated entropy based on specific frequency bands rather across all bands, as we did here.…”
Section: Discussioncontrasting
confidence: 87%
“…As predicted, we found a difference in entropy, with lower amounts of entropy during meditation compared with mind wandering. This finding contrasts with that of Vivot et al (2020), who found increased entropy of band-specific oscillations during three styles of meditation-Himalayan Yoga (FA), Vipassana (OM), and Isha Shoonya Yoga (non-dual). One reason for the difference in findings is that Vivot et al (2020) calculated entropy based on specific frequency bands rather across all bands, as we did here.…”
Section: Discussioncontrasting
confidence: 87%
“…In addition to increases in gamma power, shamanic practitioners demonstrated decreased neural signal diversity and increased criticality (i.e., PCF) in the gamma band during drumming when compared to control participants. While studies of signal diversity and criticality in non-pharmacologically induced altered states of consciousness remain scarce, a recent EEG study during meditation assessed changes in entropy and metastability (Martínez Vivot et al, 2020), which is directly related to criticality (e.g., increased metastability is associated with increased criticality). Martínez Vivot et al (2020) revealed meditative practice to be characterized by increased entropy and decreased metastability in the gamma band.…”
Section: The Shamanic State Of Consciousness Gamma Oscillations Andmentioning
confidence: 99%
“…While studies of signal diversity and criticality in non-pharmacologically induced altered states of consciousness remain scarce, a recent EEG study during meditation assessed changes in entropy and metastability (Martínez Vivot et al, 2020), which is directly related to criticality (e.g., increased metastability is associated with increased criticality). Martínez Vivot et al (2020) revealed meditative practice to be characterized by increased entropy and decreased metastability in the gamma band. This is the inverse of our findings, where shamanic practitioners had decreased neural signal diversity and increased criticality in the gamma band, which, by definition, indicates increased metastability and brain network susceptibility.…”
Section: The Shamanic State Of Consciousness Gamma Oscillations Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Speculatively, this pattern could be taken as indicating predictive processing in which higher-level coherent neural activity successfully suppresses bottom-up information flows (Bastos et al, 2020;Walsh et al, 2020). While disjoint flexibility could be viewed as a neural entropy measure in terms of independent node switching, entropy has also been associated with intelligent processing (Carhart-Harris et al, 2014;Chang et al, 2018;Cieri et al, 2021;Herzog et al, 2020;Vivot et al, 2020), and so this measure may also sometimes exhibit an inverted U relationship with psychological functioning. Qualitatively speaking, low-to-moderate levels of disjointed migration may be better than stasis/rigidity, but the non-coherent nature of node migration may tend to indicate a breakdown of adaptive functioning.…”
Section: Different Forms Of Flexibility: Disjointedness Vs Cohesivenessmentioning
confidence: 99%